MACRONUTRIENT ANALYSIS OF ORGANIC FERTILIZER FROM THE MIXTURE OF Casuarina equisetifolia LEAF LITTER AND Ananas comosus RIND WASTE WITH EFFECTIVE MICROORGANISM BIOACTIVATOR - Abdul Gani; Dinda Miftahul Jannah; Zulfadli Zulfadli (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2023)
This study aims at analyzing macronutrients of organic fertilizer from the mixture of Casuarina equisetifolia leaf litter and Ananas comosus rind waste with effective microorganism bioactivator. Research on making and analyzing the nutrient content of organic fertilizers has been carried out using a mixture Casuarina equisetifolia leaf litter and Ananas comosus rind waste which consists of three variations of the composition with two repetitions. The process of making compost is conducted by mixing small pieces of pineapple litter and rind and mixed with effective microorganism (EM4) in a container. The composting process occurs for a maximum of 31 days based on the temperature measurement of the fertilizer. In the degree of acidity test using digital pH meter, it shows that the pH level is classified as acidic, the pH variations of the fertilizer P0U1, P0U2, P1U1, P1U2, P2U1, and P2U2 are 5.029 respectively; 5,026; 4,934; 4,047; 5,452; and 4,551. The results of the analysis of the elemental nitrogen content (%) of various fertilizers P0U1, P0U2, P1U1, P1U2, P2U1, and P2U2 were 0.27; 0.38; 0.39; 0.41; 0.36; and 0.39. The results of the C-organic element analysis (%) were 25.87; 29.12; 35.58; 30.77; and 29.66. The phosphorus content (%) obtained was 0.147; 0.137; 0.138; 0.136; 0.139; and 0.142. Potassium content (%) of 0.32; 0.25; 0.56; 0.78; 1.23; and 1.79. The C / N ratio of each fertilizer variation was sequential, namely 95.81; 76.63; 83.23; 86.78; 85.47; and 76.05. The analysis parameters for C, P, and K show conformity with the National standard provisions.